Validitas Pengembangan Booklet Terintegrasi Potensi Lokal Kabupaten Pesisir Selatan pada Materi Plantae Kelas X SMA - Ratih Aulia Gusmar; Fitri Arsih; Heffi Alberida; Helsa Rahmatika (FONDATIA, 2022)
Biology is learning that can take advantage of the environment as a learning resource. Based on the results of observations and teacher interview questionnaires at SMAN 1 Lengayang that the teaching materials used by teachers and students utilize printed books and publisher's worksheets. The constraints in the teaching materials are that students find it difficult to understand the concept of plantae material, the presentation material provided is less conceptual to the student's environment, so that student learning outcomes are low. This type of research is development research using ADDIE (Analyze, Design, Development, Evaluation) mode. The research subjects were two lecturers in the biology department, FMIPA UNP, one teacher and 36 students of class X SMAN 1 Lengayang. The object of this research is an integrated development booklet of Pesisir Selatan Regency on plantae material for class X SMA. Research data is the validity of data obtained directly through the provision of questionnaire validity to the validator. The results showed that the local potential integrated development booklet met the valid category with a validity value of 88.77%. So it can be said that an integrated development booklet of the local potential of Pesisir Selatan Regency has been produced on valid high school grade X plantae material.